2015
DOI: 10.4236/jgis.2015.73021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Validation of Recent Freely-Available ASTER-GDEM V.2, SRTM V.4.1 and the DEM Derived from Topographical Map over SW Grombalia (Test Area) in North East of Tunisia

Abstract: Digital Elevation Models (DEMs) provide one of the most useful digital datasets for a wide range of users. Both the Shuttle Radar Topographic Mission (STRM V.4.1) topography and the Advanced Spaceborne Thermal Emission and Reflection Radiometer Global Digital Elevation Model (ASTER-GDEM V.2) have been widely used in geomorphology, hydrology, tectonic, and others since they were made access to the public. The magnitude of vertical errors of two near-global DEMs-SRTM and ASTER-GDEM is compared and validated agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Furthermore, the horizontal error is stated to be an East/West shift of −0.13 arc-seconds and North/South shift of 0.19 arc-seconds when compared to the 10-m mesh DEM produced by the Geographical Survey Institute (GIS) of Japan [34] [35]. Recent studies were carried out on the earth's lowest elevation: the Dead Sea (Jordan) to test the validity of ASTER DEM [36], and to compare ASTER DEM, and SRTM (the Shuttle Radar Topographic Mission) DEM against a referenced DEM constructed from 1:25,000 scale topographic map [37]. It is reported that the overall accuracy of the DEM is in line with the reported official accuracy specifications [36].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the horizontal error is stated to be an East/West shift of −0.13 arc-seconds and North/South shift of 0.19 arc-seconds when compared to the 10-m mesh DEM produced by the Geographical Survey Institute (GIS) of Japan [34] [35]. Recent studies were carried out on the earth's lowest elevation: the Dead Sea (Jordan) to test the validity of ASTER DEM [36], and to compare ASTER DEM, and SRTM (the Shuttle Radar Topographic Mission) DEM against a referenced DEM constructed from 1:25,000 scale topographic map [37]. It is reported that the overall accuracy of the DEM is in line with the reported official accuracy specifications [36].…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, SRTM DEM is comparatively more accurate than ASTER DEM, but with 90 m resolution, whereas, ASTER DEM is of 30 m spatial resolution. However, both DEMS are employed heavily at present to delineate watershed and sub-watershed boundaries, and drainage networks, to derive and calculate drainage morphometric information, and to establish cross sections [37]. Considering the Ras En Naqb area, which consists mostly of bare land and arid climate, along with the availability of ASTER DEM (30 m spatial resolution), and the Arc GIS tools, both were employed to derive, and calculate the morphometric parameters of the Ras En Naqb watersheds.…”
Section: Methodsmentioning
confidence: 99%
“…In Nigeria, Menegbo and Doosu [31] demonstrated that SRTM-V4.1 and ASTER-V2.1 DEM absolute vertical accuracies with reference to GPS ground control station are, respectively, ± 6.30 m and ± 8.86 m. Using a large scale topographic map for validation purposes in north-east of Tunisia, Ouerghi et al [32] showed a satisfactory vertical accuracies ± 7.62 m for SRTM and ± 10.53 m for ASTER. They also discussed the significant accuracy of watershed delineation and drainage system extraction using SRTM-V4.1 data than ASTER-V2.1 DEM.…”
Section: Aster and Srtm Dems Accuracies Assessment: Literature Reviewmentioning
confidence: 99%
“…A DEM can be acquired from different sources, including ground-based surveys [ 15 , 16 , 17 , 18 ], basic topographic maps [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ] and remote sensing technique [ 8 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Many studies have been simultaneously conducted with the DEM generation by using interferometry synthetic aperture radar (InSAR) technique [ 9 , 27 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%